METHODS FOR DEVELOPING FLUENT SPEECH IN PRESCHOOL CHILDREN - А. С. Курбонов; Т. В. Ботиров (Web of Journals Publishing, 2025)
Control system synthesis algorithms for automating the pulley cover assembly process in the production of an autogenerator play a key role in improving the efficiency and quality of production processes. Modern automation technologies make it possible to optimize the operations associated with the assembly of components, which is especially important in the automotive industry, where the reliability and accuracy of manufactured products are critical. The technological process of assembling pulley covers in the production of an autogenerator requires an integrated approach, including the synthesis of the control system, control over compliance with assembly parameters and minimization of errors.